2006
DOI: 10.1590/s0103-84782006000400038
|View full text |Cite
|
Sign up to set email alerts
|

Alterações post-mortem em tambaqui (Colossoma macropomum) conservados em gelo

Abstract: RESUMO Este estudo apresenta a avaliação da qualidade de tambaqui (Colossoma macropomum) conservado em gelo. Foi determinado o tempo de vida útil por meio de avaliações sensoriais e análises de pH e bases voláteis totais (N-BVT) no

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 3 publications
2
6
0
4
Order By: Relevance
“…Odor and general appearance increased slowly, while the attributes related to the eyes ("transparency", "pupil" and "eye shape") and gills ("color" and "odor") presented the highest loss of freshness. These results agree with Almeida et al (2006) who observed that the first changes in tambaqui stored in ice included a larger amount of mucus on the gills and a smooth deformation of the eyes caused by friction with the ice. The autolytic reactions caused by the increased storage time, combined with the water absorption from the melting ice, make the observation of the eyes and evaluation of their quality attributes more difficult and confusing to the jury .…”
Section: Discussionsupporting
confidence: 92%
“…Odor and general appearance increased slowly, while the attributes related to the eyes ("transparency", "pupil" and "eye shape") and gills ("color" and "odor") presented the highest loss of freshness. These results agree with Almeida et al (2006) who observed that the first changes in tambaqui stored in ice included a larger amount of mucus on the gills and a smooth deformation of the eyes caused by friction with the ice. The autolytic reactions caused by the increased storage time, combined with the water absorption from the melting ice, make the observation of the eyes and evaluation of their quality attributes more difficult and confusing to the jury .…”
Section: Discussionsupporting
confidence: 92%
“…Mendes (2013) found a TVB-N variation in tambaquis, increasing from 15.14 to 32.19 g kg -1 TVB-N at 35 days of ice storage, similar to that reported by Almeida et al (2006). Sensory analysis showed that the quality of the tambaquis slaughtered by asphyxia was lower after 7 to 21 days of storage.…”
Section: Discussionsupporting
confidence: 63%
“…Batista et al (2004) observed that farmed matrinxãs kept in ice initially exhibited lower pH values, increasing after 6 days. Almeida et al (2006) observed pH between 6.07 and 6.66 in farmed tambaquis kept in ice for 43 days, with a small variation in the first days of storage and a significant increase after 19 days. Similar results were also observed by Concollato et al (2016) and Castro et al (2016).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The total lipid content of the fish-farmed tambaqui was lower than that found in tambaqui (C. macropomum), the total lipid (7.6%) by Almeida et al 22 and by Maia and Rodriguez-Amaya 16 (6.3%) but higher than that found by Arbeláez-Rojas et al 23 (2.4%). The differences in these results could be related to the handling and farming conditions used in each situation.…”
Section: Resultsmentioning
confidence: 52%